Hydraulic Power Engineering - National Resource of Belarus - S. B. Belyi; V. V. Gerasimov; O. F. Yakushko; P. S. Lopukh; L. P. Batyan; L. D. Burko; P. A. Mitrakhovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The main reason of return to so called «small hydraulic power engineering», involvement of local hydraulic power resources in power balance of the Republic is significant changes of social and economical conditions of management, acute deficit and high price of local and in^orted resources of fuel, oil, gas, electric power, respectively.The paper analyses hydraulic power engineering potential of the Republic of Belarus. History of the development of hydraulic power engineering in the Republic, program of restoration and construction of hydraulic power stations, some prospective projects that ate planned for realization are presented in the paper.